PROFIL KLINIKOPATOLOGI KARSINOMA LARING DI RSUD DR SOETOMO, SURABAYA 2018-2021 - Djuanda, Stephanie Natasha; Kusumastuti, Etty Hary; Ariani, Grace (Majalah Patologi Indonesia, 2025)
Introduction Laryngeal carcinoma is the second most common malignancy of the respiratory tract1. Based on 2020 Global Cancer Observatory data, the incidence rate of laryngeal carcinoma is 184,615 cases with a mortality rate > 50%2. There are some prognostic factors that predict the prognosis and 5 year survival rate of the patients. Study of this factor is very important because it will affect the patient's management 1,3.The clinicopathological profile is very important in laryngeal carcinoma because the majority of specimen are received in the small biopsies. Methods This research is observational descriptive study with a retrospective approach. Population of this study are paraffin blocks obtained from biopsy and surgical that had been diagnosed histopathologically as laryngeal carcinoma in the Dr. Soetomo General Academic Hospital from January 2018 - December 2021. Demographic, radiologic and histopathology data were taken from the patient's medical records. Results The majority patients were males (93%). The average age of patients was 59 (±5.91) years, with age range is 27 – 84 years, peak incidence were in 61-70 years (34.1%). The tumor located mostly in glottic (60.2%). Based on the T and N staging, most patient came at T4 and N2 stage. All the tumor were conventional squamous cell carcinoma. Conclusion Clinicopathology profile is very important in determine the prognostic factor in laryngeal carcinoma. Most of patient were males, in age group 61-70 years, located in glottis. Most patient came at advanced stadium. Most tumor were conventional squamous cell carcinoma, and the majority was well differentiated grade.